INCOME SHIFTING DAN PEMANFAATAN NEGARA TAX HAVEN - Pramesthi, Rr. Dyah Fadliela; Suprapti, Eny; Kurniawati, Eris Tri (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this research is to examine the influence of income shifting strategy to tax haven country utilization. The dependent variable is tax haven country utilization and the independent variable was income shifting strategy proxied by multinational, transfer pricing, thin capitalization, and intangible asset. The samples are 32 manufacturer basic and chemical industry sector companies listed in Indonesia Stock Exchange from, 2015-2017. The analysis method is data panel regression by using Eviews 7. The result of this research shows that income shifting which is proxied by multinational and transfer pricing have positive influence to tax haven country utilization but income shifting strategy which are proxied by thin capitalization and intangible asset have no significant influence to tax haven country utilization.Â